Effects of age of quails, coturnix coturnix japonica and storage period of carcass on the pH, weight loss and the shelf life when stored at 4 °C - Wan Siti Khadijah Aisyah Wan Husin (2013)
Three studies were conducted in order to fulfill the aim of this study which is to determine the effects of age and the storage period on pH, weight loss and microbial condition of three different age groups of quail carcass. Young quail carcass (3 weeks old), mature quail carcass (9 weeks old) and spent quail carcass (36 weeks old) were used in this experiment. Results showed that there was no statistically significant different (i.e. p>0.05) between age of quails on the bacterial count and weight loss of the quail carcass during aerobic storage of 4°C. However, age has an effect on pH value of quail carcass stored at 4°C. There was a significance difference in the pH value observed on day 3 between young quail (6.33±0.0) and spent quail (6.10±0.03). From the findings, there is also an evidence of that storage period will increased the microbial loads. There was a statistically significant different (i.e. p>0.05) observed between period of storage on the bacterial count, pH and weight loss of the quail carcass during aerobic storage of 4°C.